Analisis Kebutuhan Parkir pada Gedung Pusat Informasi dan Perpustakaan serta Sekolah Pascasarjana Universitas Negeri Padang - Dita Rora Efendi; Rizky Indra Utama; Oktaviani Oktaviani; Muhammad Ihsan (YASIN, 2026)
The availability of adequate parking facilities is an important factor in supporting the smooth operation of activities within higher education institutions, particularly in areas with high vehicle mobility, such as the Information and Library Center Building (GPIP) and the Graduate School (GSPs) of Universitas Negeri Padang. This study aims to analyze parking characteristics, parking space demand and availability, and formulate appropriate parking management for the research area. This study used a descriptive quantitative method with field survey techniques and direct observation. Data collection was conducted over three days, namely 14–16 April 2026, from 06:00 to 18:00 Western Indonesia Time, with data including the number of vehicles entering and leaving, parking duration, parking accumulation, parking volume, parking capacity, and the existing condition of parking facilities. The results show that the GPIP area has a high level of parking utilization, with a combined motorcycle parking index of 1.40 on Tuesday, 1.77 on Wednesday, and 1.34 on Thursday. The highest car parking index in the GSPs area reached 1.14. The highest parking demand occurred in the UNP Mart area, at 125 parking space units (SRP), while the available parking capacity in the GPIP area was 340 SRP and in the GSPs area was 21 SRP. The analysis results show that the main parking problem is caused by the uneven distribution of parking space use. The conclusion of this study emphasizes that optimizing parking facilities requires parking management based on the redistribution of vehicles to areas that still have available capacity. The practical implications of this study include the need for parking line arrangement, vehicle circulation management, signage installation, and improved parking supervision so that the utilization of parking facilities in the campus area can operate more effectively.